Pre-existing pulmonary fibrosis is associated with adverse outcomes after lung resection. (December 2022) - Garner, Megan; Taylor, Marcus; Smith, Matthew; Abah, Udo; Shackcloth, Michael; Granato, Felice; Rammohan, Kandadai; ,
Abstract: Introduction: Pulmonary fibrosis is a risk factor for the development of lung cancer. However, the low incidence of the pathology means that it is not well represented in thoracic surgery risk scoring systems. We aimed to assess whether short and long-term outcomes after lung resection for primary lung cancer were worse in patients with pre-existing pulmonary fibrosis. Methods: A total of 5029 consecutive patients undergoing lung resection for primary lung cancer between 2012 and 2018 in two UK centres were included. Primary outcomes were 90-day & 1-year mortality, post-operative complications and overall survival. Univariable analyses were used to compare outcomes between patients with and without pre-existing pulmonary fibrosis. Results: In total, 0.7% (n = 33) of patients had a pre-existing diagnosis of pulmonary fibrosis (idiopathic pulmonary fibrosis 48.5%, non-specific interstitial pneumonia 6.1%, unknown 45.5%). Overall, 90-day and 1-year mortality were all significantly higher amongst patients with fibrosis (90-day: 18.2% vs 3.6%, p < 0.001; 1-year: 36.4% vs 10.7%, p < 0.001). The rate of reintubation was significantly higher for patients with fibrosis (9.1% vs 2.9%, p = 0.038) yet there was no difference in post-operative length of stay between groups (fibrosis: 6 days [IQR 4–9 days] vs non-fibrosis: 5 days [IQR 4–8 days], p = 0.675). Overall survival was also significantly reduced for patients with pulmonary fibrosis (log-rank analysis, p < 0.001). Conclusions: Despite its small size, this study suggests that short and long-term outcomes after lung resection are worse for patients with pre-existing pulmonary fibrosis. Segmental resections could be considered in these patients where oncologically appropriate to minimise peri-operative risk. Highlights: Pulmonary fibrosis patients are a small subgroup of lung resection patients. Pulmonary fibrosis patients had higher 90-day mortality after lung resection. Mortality was highest for pulmonary fibrosis patients experiencing re-intubation. Overall survival was worse for pulmonary fibrosis patients after lung resection.